High-throughput nanopore targeted sequencing for efficient drug resistance assay of Mycobacterium tuberculosis - Tang, Chen; Wu, Lianpeng; Li, Machao; Dai, Jianyi; Shi, Ye; Wang, Qiongdan; Xu, Feng; Zheng, Laibao; Xiao, Xingxing; Cai, Junwen; Zhang, Yanjun; Yang, Yuting; et al. (Frontiers in Microbiology, 2024)
Drug-resistant tuberculosis (TB), especially multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB), is one of the urgent clinical problems and public health challenges. Culture-based phenotypic drug susceptibility testings (pDSTs) are time-consuming and PCR-based assays are limited to hotspot mutations. In this study we developed and validated a convenient and efficient approach based on the high-throughput nanopore sequencing technology combined with multiplex PCR, namely nanopore targeted sequencing (NTS), to simultaneously sequence 18 genes associated with antibiotic resistance in Mycobacterium tuberculosis (MTB). Analytical performance of NTS was evaluated, and 99 clinical samples were collected for evaluation of NTS clinical performance. The NTS results showed that MTB and its drug resistance was successfully identified in about 7.5 hours. Furthermore, while compared to pDST and Xpert MTB/RIF assay, NTS provided much more drug resistance information with 14 anti-TB drugs, and 20 clinical MTB drug-resistant cases were revealed. The mutations underlying these drug-resistant cases were all verified by Sanger sequencing. Our approach for this TB drug resistance assay possesses the advantages of culture-free, efficiency, high-throughput, and high accuracy, which would be very helpful for clinical patient management and TB infection control.